Organicism and Construction in Nielsen’s Symphony No. 5 - Fjeldsøe, Michael (Carl Nielsen Studies, 2003)
This article points to the fact, that most analytical approaches to Nielsen’s music are embedded in an underlying modernist discourse shared by its opponents, in which construction and cromaticism are considered as opposed to organicism and diatonicism. Analysing the melodic and interval structures at the beginning of Nielsen’s Fifth Symphony it can be shown that Nielsen develops a system of recurring symmetrical intervallic structures, which are not based on the octave or any traditional modes. Construction and organicism enter a state of interdependence, where consistent organicism brings about the construction of a network of fixed pitches; and this construction enables the setting free of melodic organicism from the demands of inherited keys or modes.